2006
DOI: 10.1007/s00792-006-0514-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of a novel β-1,3-glucanase from alkaliphilic Nocardiopsis sp. strain F96

Abstract: Alkaliphilic Nocardiopsis sp. strain F96 produced three beta-1,3-glucanase isozymes of different molecular masses (BglF1, BglF2 and BglF3). The N-terminal amino acid sequences of BglFs indicated that these isozymes were the products of a single gene. The beta-1,3-glucanase gene (bglF) was cloned from the chromosomal DNA of strain F96. The bglF gene encoded a polypeptide of 270 amino acids including a signal sequence. The deduced amino acid sequence of mature BglF exhibited the highest homology to those of glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 15 publications
1
37
0
Order By: Relevance
“…This thermostable enzyme could be put to use for preparing high-fructose syrups. Such syrups are extensively preferred β-1,3-1,4-glucans rather than β-1,3-glucans; cloning and expression; crystal structure; construction and characterization of chimeras Masuda et al 2003Masuda et al , 2006Fibriansah et al 2006Fibriansah et al , 2007Koizumi et al 2007Koizumi et al , 2009 Alkali-tolerant thermostable inulinase Xylan bioconversion into xylose for different products Tsujibo et al 1990aTsujibo et al , 1991 used in the beverage industry as sweeteners for making soft drinks (Van der Maarel et al 2002). Another recent paper describes the isolation and immobilization of a thermostable α-amylase derived from a haloalkaliphilic marine isolate referred to as Nocardiopsis sp.…”
Section: Carbohydrases Obtained From Nocardiopsis Speciesmentioning
confidence: 99%
“…This thermostable enzyme could be put to use for preparing high-fructose syrups. Such syrups are extensively preferred β-1,3-1,4-glucans rather than β-1,3-glucans; cloning and expression; crystal structure; construction and characterization of chimeras Masuda et al 2003Masuda et al , 2006Fibriansah et al 2006Fibriansah et al , 2007Koizumi et al 2007Koizumi et al , 2009 Alkali-tolerant thermostable inulinase Xylan bioconversion into xylose for different products Tsujibo et al 1990aTsujibo et al , 1991 used in the beverage industry as sweeteners for making soft drinks (Van der Maarel et al 2002). Another recent paper describes the isolation and immobilization of a thermostable α-amylase derived from a haloalkaliphilic marine isolate referred to as Nocardiopsis sp.…”
Section: Carbohydrases Obtained From Nocardiopsis Speciesmentioning
confidence: 99%
“…Recombinant plasmids pET-BglF bearing the bglF gene from strain F96 16) and pET-B bearing the ChBD region of the chiJ gene from strain J813 21) were used. Plasmid pBG200 contains the bglH gene from B. circulans IAM1165.…”
Section: Methodsmentioning
confidence: 99%
“…15) It has been shown that strain F96 also produces an endo--1,3-glucanase. 16) The -1,3-glucanase gene (bglF) was cloned from the chromosomal DNA of strain F96. It encoded a polypeptide comprising a signal peptide (25 amino acids) and mature enzyme (245 amino acids).…”
mentioning
confidence: 99%
“…F96 (2HYK), 50 which exhibits an uncharacteristic preference for mixed linked b-1,3-1,4-glucans (typically lichenin). 51 Eighteen amino acid residue pairs with P* [ 20 were identified (Table II). As with other GH16 cluster comparisons, the N-terminal regions in the primary sequences of each subfamily are poorly aligned; in this case, consistent secondary structure agreement between P. tremula XTH and Nocardiopsis glucanase did not occur until the second major b-strand of each protein (XTH residues 51-61 and glucanase residues 88-95), suggesting that P* 5 2070 for the Gly44/Gly71 pair is a false positive.…”
Section: Figurementioning
confidence: 99%